Healthcare Support for Elderly in Pandemic Context Using Ehealth Systems - Eugenia TIRZIU; Eleonora TUDORA; Maria GHEORGHE-MOISII; Ovidiu BICA (Communications of International Proceedings, 2021)
The COVID-19 pandemic had a major impact on the faster evolution of the digitalization of medical services. Thus, new technological advances bring new opportunities and life-saving solutions to humanity in times of critical pandemic and provide solutions to help isolated coronavirus patients, as well as people with chronic conditions. The use of eHealth monitoring systems at home offers major opportunities for both the protection of physicians and elderly patients’ life in situations involving isolation. This paper presents the current approach of eHealth systems as a safe proactive measure to improve care, the benefits of eHealth systems, opportunity to use eHealth systems in the context of new pandemics and future trends for e-health systems. To demonstrate the potential of healthcare support, is presented the case study of the eHealth home monitoring system: RO-SmartAgeing highlighting healthcare support provided during pandemics.
Keywords: Healthcare Support; Pandemic; Ehealth Systems; Elderly.